The effects of ownership structure on corporate performance - Sidi, Selim. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1996., 1996)
It has been suggested that when the ownership of a firm is dispersed, its managers will deviate from profit-maximizing behaviour. Furthermore, there is an asymmetry for these managers between the consequences of outstanding success and severe failure. Moreover, managers utility tends to increase with firm size. Hence, the managerial theory of the firm' says that manager-controlled firms will be less profitable, will tend more to avoid risky decisions anc grew faster than owner-controlled firms. On the other hand, other scholars have pointed out that there are also benefits associated with the disoersed ownership corporation. Thus, the effects of ownership structure on corporate performance have been a focus of research in Western countries. The opening of the Istanbul Stock Exchange has introouced an increasing degree of ownership dispersion in Turkey too, a phenomenon that is expected to intensify in the coming years with the increasing prominence of the stock exchange. Therefore, we undertake a research on a sample of firms selected from the Istanbul Stock Exchange concerning the profitability, capital structure and growth of firms and using data from the Exchange's Yearbook of Companies. Running regressions and ANOVAs we see that dispersed ownership firms are somewhat more profitable and grow faster. We also find out that firms with major-financial-institutional shareholders are less profitable in Turkey. At the end of our research, we suggest some reasons for these phenomena.
Keywords: Corporate profits.; Stock ownership.